A Comprehensive Clinical Acumen Enhanced by Point-of-Care Ultrasonography in Managing Acute Life-Threatening Massive Pulmonary Thromboembolism in a Peripheral Setting: A Case Report - Prabhav Chhaperwal; Sudhir Kumar; Gurbinder Suri; Uma Garg; Suraj Kapoor; Bhargava Devarakonda (Annals of Cardiac Anaesthesia)
Acute massive pulmonary thromboembolism (PTE) is a potentially life-threatening condition requiring urgent management to decrease mortality. However, in the peripheral setting, managing the emergency can be challenging. We report a case of massive PTE presenting with cardiopulmonary arrest, successfully managed with advanced cardiac life support, early initiation of anticoagulants (heparin), and thrombolytics. This case report explores the successful management of a critically ill patient presenting with massive pulmonary embolism in a peripheral healthcare facility, emphasizing the importance of a well-coordinated approach in such challenging environments. The approach in the case included recognizing the challenge with timely provisional diagnosis, initial stabilization, hemodynamic support, early consideration for anticoagulants, and thrombolysis after supporting provisional diagnosis with point-of-care ultrasonography (POCUS), team effort, and administrative support in Cas Evac to the tertiary care center. Timely administration of heparin and thrombolytics may serve as potential life-saving measures in peripheral settings, along with the availability of an ultrasound machine. Managing acute life-threatening massive PTE in peripheral settings requires a strategic and resourceful approach. Timely administration of heparin and thrombolytics may serve as potential life-saving measures. However, the administration of thrombolytics in PTE needs the support of POCUS to make quick decisions in peripheral settings. Collaboration between peripheral and advanced tertiary care healthcare facilities is crucial to ensure optimal outcomes for patients experiencing this critical condition.